High-strength and high-conductivity copper alloy sheet and method for producing the same
By controlling the silver content and structure in Cu-Ag alloy and adopting a multi-process manufacturing method, the problem of difficulty in improving the strength and conductivity of Cu-Ag alloy sheets is solved, and a copper alloy sheet with high strength and high conductivity is realized. Suitable for a variety of electronic devices.
Patent Information
- Application Number
- CN202210960520.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-08-10
- Filing Date
- 2018-08-10
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2038-08-10
AI Technical Summary
Existing Cu-Ag alloy sheets are difficult to meet the requirements of high strength and high conductivity at the same time, and are prone to loosening, undulating or bending during the manufacturing process, resulting in difficulty in thickness control and uneven processing rate, and it is impossible to make large areas or thick walls. plate.
By adding 4-13 mass% silver to the Cu-Ag alloy and adopting the processes of casting, cold rolling, solid solution treatment, heat treatment and re-cold rolling, the content and structural structure of the silver are controlled to improve the tensile strength of the alloy and Conductivity ensures the mechanical and electrical properties of the sheet.
Cu-Ag alloy sheets with high strength and high conductivity are suitable for water-cooled copper magnets, contact probes and connectors for portable devices. They can withstand huge electromagnetic stresses and fast charging, and are under miniaturization and high density conditions. Maintain excellent performance.
Smart Images

Figure CN115449662B_ABST
Abstract
Description
[0001] This application is a divisional application of an invention patent application with an application date of August 10, 2018, an application number of 201880061145.9 (international application number of PCT / JP2018 / 030132), and an invention name of “High-strength and high-conductivity copper alloy sheet material and its manufacturing method”. Technical Field
[0002] The present invention relates to a high-strength and high-conductivity copper alloy sheet material and a method for producing the same. Background Art
[0003] In various electrical / electronic industrial fields, conductive plates are required as conductive components with high strength and high conductivity. As such conductive plates, copper alloy (Cu-Ag alloy) plates containing silver are being developed. For example, in a water-cooled copper magnet, a bit plate is used as a conductive plate for generating a strong magnetic field, and a bit coil using the bit plate is used. The bit plate is required to have a strength sufficient to withstand huge electromagnetic stress and water pressure during water cooling, and a conductivity that can suppress heat generation even when a large current is flowing. In such a bit plate, Cu-Ag alloy plates are being used, but Cu-Ag alloy plates that meet sufficient strength and conductivity are not necessarily available, and it is required to further improve the strength and conductivity of the Cu-Ag alloy plates at the same time.
[0004] In addition, for electronic devices, multifunctionalization, high integration, miniaturization, etc. are being carried out. Along with this, the contact probes used in the inspection of electronic devices are also required to be more miniaturized and more dense than before. In order to cope with the miniaturization and high density of the contact probes, it is necessary to miniaturize and densify the probes themselves as the conductive parts, so high-strength materials are required. In addition, in order to suppress the increase in resistance caused by the reduction in the cross-sectional area of the conductive part due to miniaturization and high density, materials with high conductivity are required. In addition, in order to achieve an improvement in detection sensitivity, high conductivity is also required for the materials used for the probes. In the past, as probe materials, conductive materials that meet the strength and conductivity as described above have not yet been obtained.
[0005] Portable devices are required to be able to be used for a long time after charging once, so the rechargeable batteries used in portable devices are being miniaturized and increased in capacity. In addition, recently, the high speed and multifunctionality of portable devices have increased power consumption, so the large capacity of rechargeable batteries has become increasingly important. When the rechargeable battery has a large capacity, it takes more time to charge, so fast charging is required. In fast charging, more current flows in a short time, so it is necessary to reduce the resistance of the conductor or increase the cross-sectional area of the conductor. Due to the miniaturization of portable devices, it is impossible to increase the size of components, so there is a limit to increasing the cross-sectional area, and the connector also requires a material with high conductivity. In addition, with the miniaturization of portable devices, the connector is also required to be miniaturized, so the connector material is also required to have high conductivity and high strength. In the past, as a connector material, a conductive material that meets the strength and conductivity as described above has not yet been obtained.
[0006] In the composition and manufacturing method of the existing Cu-Ag alloy sheet material, there is no material that satisfies the strength and conductivity as described above. In addition, regarding the wire of Cu-Ag alloy, a manufacturing method of Cu-Ag alloy wire with high strength and high conductivity and a wire using the manufacturing method are proposed. However, even if you want to use Cu-Ag alloy wire as a raw material to manufacture a sheet, it is practically impossible to obtain a Cu-Ag alloy sheet. That is, when the Cu-Ag alloy wire is rolled to make a sheet, it becomes rolled without post-tension, so the raw material wire is loose during rolling, resulting in undulations or bending. Therefore, the thickness of the sheet cannot be controlled, and cracks are easily generated. In addition, since the thickness control is difficult, the processing rate varies according to the part, and the strength and conductivity also increase according to the part. Therefore, it is practically impossible to make a sheet. In addition, large-area and thick-walled sheets cannot be made, especially bit plates.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 6-073515
[0010] Patent Document 2: Japanese Patent No. 2714555
[0011] Patent Document 3: Japanese Patent Application Publication No. 2000-199042 Summary of the invention
[0012] An object of the present invention is to provide a high-strength and high-conductivity copper alloy sheet material that can be practically applied to conductive members requiring the above-mentioned strength and conductivity, and a method for producing the same.
[0013] The high-strength and high-conductivity copper alloy sheet material according to an embodiment of the present invention is characterized in that silver is contained in a range of 6 mass % to 13 mass %, the balance being copper and inevitable impurities, a minimum tensile strength (UTS) of 1000 MPa to 1250 MPa, and a conductivity (%IACS) of 60% to 90%.
[0014] A high-strength and high-conductivity copper alloy sheet material according to another embodiment of the present invention is characterized in that silver is contained in a range of 4 mass % to 13 mass %, the remainder being copper and inevitable impurities, and in a diffraction pattern of X-ray diffraction of the copper alloy sheet material, a peak intensity ratio of the (311) plane of silver is 20% or less.
[0015] The method for manufacturing a high-strength and high-conductivity copper alloy sheet material based on an embodiment of the present invention is characterized in that it comprises: a step of casting an alloy raw material containing silver in a range of 4 mass % to 13 mass %, with the balance consisting of copper and inevitable impurities, to obtain an ingot; a step of cold rolling the ingot to obtain a first rolled material; a step of solution treating the first rolled material at a temperature of 700° C. to 780° C. to obtain a solution treated material; a step of cold rolling the solution treated material to obtain a second rolled material; a step of heat treating the second rolled material at a temperature of 200° C. to 8 hours to 48 hours, thereby performing an aging treatment to obtain an aging treated material; and a step of cold rolling the aging treated material to obtain a third rolled material as a copper alloy sheet material.
[0016] Effects of the Invention
[0017] According to the present invention, it is possible to provide a high-strength and high-conductivity copper alloy sheet material which can be practically applied to a conductive member requiring strength and conductivity, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the X-ray diffraction spectrum of the copper alloy plate material of Example 29.
[0019] Figure 2 This is the X-ray diffraction spectrum of the copper alloy plate material of Comparative Example 9. DETAILED DESCRIPTION
[0020] Hereinafter, embodiments for implementing the high-strength and high-conductivity copper alloy sheet material and the method for producing the same according to the present invention will be described.
[0021] (First Embodiment)
[0022] The high-strength and high-conductivity copper alloy sheet material of the first embodiment is a copper alloy (Cu-Ag alloy) sheet material containing silver (Ag) in the range of 6 mass % or more and 13 mass % or less, and the balance is composed of copper (Cu) and inevitable impurities. When the content of Ag in the Cu-Ag alloy sheet material is less than 6 mass %, the strength improvement effect brought about by the inclusion of Ag cannot be obtained. In terms of further improving the strength of the Cu-Ag alloy sheet material, the content of Ag is preferably 8 mass % or more, and more preferably 9 mass % or more. When the content of Ag exceeds 13 mass %, the processability is reduced, and it is difficult to manufacture the Cu-Ag alloy sheet material in practice. In terms of further improving the processability of the Cu-Ag alloy sheet material, the content of Ag is preferably 12 mass % or less, and more preferably 11 mass % or less.
[0023] In the high-strength and high-conductivity copper alloy sheet of the embodiment, the inevitable impurities other than Cu and Ag contained in the Cu-Ag alloy sheet are not particularly limited, and their content is preferably 0.1% by mass or less. When the impurity content exceeds 0.1% by mass, the strength and conductivity of the Cu-Ag alloy sheet may be reduced. The content of inevitable impurities is further preferably 0.01% by mass or less. It should be noted that in the high-strength and high-conductivity copper alloy sheet of the embodiment, a third element other than Cu and Ag may be included according to the circumstances within the range that does not impair the mechanical properties, electrical properties, properties of the metal structure, etc. As such a third element, gold (Au), aluminum (Al), bismuth (Bi), manganese (Mn), antimony (Sb), magnesium (Mg), samarium (Sm), etc. can be listed.
[0024] The high-strength and high-conductivity Cu-Ag alloy sheet material of the embodiment has a tensile strength (UTS) of more than 1000MPa and less than 1250MPa and a conductivity (%IACS) of more than 60% and less than 90%. It should be noted that the tensile strength (UTS) in the specification of this application represents a minimum value. By utilizing such a Cu-Ag alloy sheet material that combines high strength and high conductivity, a conductive component (sheet material) suitable for, for example, a bit plate (conductive plate) used in a water-cooled copper magnet, a probe material for a contact probe, a connector material for a portable device, etc. can be provided. That is, when the tensile strength (UTS) of the Cu-Ag alloy sheet material is more than 1000MPa and the conductivity (%IACS) is more than 60%, in addition to satisfying the strength required by the conductive component (sheet material), the conductivity of the conductive component can also be further improved. However, for Cu-Ag alloy sheets containing Ag in the range of 6 to 13 mass%, a tensile strength (UTS) exceeding 1250 MPa and a conductivity (%IACS) exceeding 90% are not practical. Even if such values can be achieved, it is difficult to maintain the shape of the sheet and the workability of the sheet.
[0025] For example, when the high-strength and high-conductivity Cu-Ag alloy plate of the embodiment is applied to the bit plate of the water-cooled copper magnet, in addition to being able to withstand huge electromagnetic stress and water pressure during water cooling, it is also possible to suppress heat generation even when a large current is flowing. In addition, the Cu-Ag alloy plate is also suitable as a probe material for a contact probe and a connector material for a portable device. When the high-strength and high-conductivity Cu-Ag alloy plate of the embodiment is used as a probe material for a contact probe, in addition to satisfying the strength that can achieve miniaturization and high density of the probe, it is also possible to suppress the increase in resistance even when the cross-sectional area of the probe is reduced due to miniaturization and high density. In addition, when the high-strength and high-conductivity Cu-Ag alloy plate of the embodiment is used as a connector material for a portable device, it is possible to maintain the shape and function of the connector while miniaturizing it so that a large amount of current that can cope with fast charging can be circulated in a short time, and miniaturization that can cope with portable devices is achieved.
[0026] When a Cu-Ag alloy sheet is produced by a manufacturing process including rolling and heat treatment described later, the tensile strength (UTS) generally differs depending on the direction of pressure application in the rolling process of the sheet manufacturing process, that is, the rolling direction and the direction orthogonal to the rolling direction (the direction at 90° to the rolling direction). Here, the rolling direction refers to the direction perpendicular to the axial direction of the working roll of the rolling mill, and the direction orthogonal to the rolling direction refers to the axial direction of the working roll of the rolling mill. The high-strength and high-conductivity Cu-Ag alloy sheet of the embodiment satisfies a tensile strength (UTS) of 1000 MPa or more in either the rolling direction or the direction orthogonal to the rolling direction.
[0027] In addition, for the high-strength and high-conductivity Cu-Ag alloy sheet of the embodiment, the minimum value of the tensile strength (UTS) in the rolling direction satisfies 1000MPa or more and 1150MPa or less, and the minimum value of the tensile strength (UTS) in the direction orthogonal to the rolling direction satisfies 1150MPa or more and 1250MPa or less. The tensile strength in the rolling direction of the existing Cu-Ag alloy sheet is low, and in contrast, the tensile strength (UTS) in the rolling direction of the high-strength and high-conductivity Cu-Ag alloy sheet of the embodiment also satisfies 1000MPa or more and 1150MPa or less. Therefore, when the Cu-Ag alloy sheet of the embodiment is used as a conductive component, even when stress and pressure are applied to the conductive component from various directions, such stress and pressure can be tolerated. As a result, the practicality of the Cu-Ag alloy sheet can be greatly improved.
[0028] Here, the tensile strength (UTS) specified in the specification of this application is the stress value under the state of applying the maximum load in the tensile test, which represents the ultimate tensile strength (Ultimate Tensile Strength). Regarding the tensile strength (UTS) specified in the specification of this application, a test piece (standard test piece) with a width of 10 mm, a thickness of 0.2 mm, and a length of 200 mm is basically used. In the tensile test with the chuck speed set to 100 mm / min, the load is applied until it breaks, and the strength (unit: MPa) at the moment when the maximum load is applied is used as the tensile strength (UTS). However, the size of the test piece is not limited to the above-mentioned shape. The test piece only needs to have a size that can be clamped under the use conditions of the tensile tester. For example, a test piece with a width of 2 mm, a thickness of 0.2 mm, and a length of 10 mm can be used. As long as a test piece with a size that can be used to implement a tensile test using a tensile tester is used, the tensile strength (UTS) as the measured value is substantially the same. It should be noted that the values of the tensile strength in the rolling direction (UTS) and the tensile strength in the direction orthogonal to the rolling direction (UTS) are set to the values obtained by cutting test pieces from more than 3 locations of each sample to carry out the tensile test and representing the minimum value of these measured values. Instead of cutting test pieces from more than 3 locations of a sample to carry out the tensile test, any three or more test pieces may be prepared. The value of the tensile strength in the direction during unspecified rolling (UTS) represents the minimum value of the measured values of more than 3 test pieces prepared regardless of the rolling direction. When the rolling direction cannot be specified, the tensile strength (UTS) in one direction and the direction orthogonal to the rolling direction may be measured separately in the sample, and the direction may be inferred by considering the magnitude of these values.
[0029] In the high-strength and high-conductivity Cu-Ag alloy sheet of the embodiment, the electrical conductivity (%IACS) is 60% to 90%. The electrical conductivity (%IACS) of the Cu-Ag alloy sheet of the embodiment is preferably 64% to 75%, more preferably 66% to 75%, and even more preferably 70% to 75%. Here, the electrical conductivity (%IACS) is a standard representing the electrical conductivity based on IACS (international annealed copper standard), which is the annealed standard soft copper (volume resistivity: 1.7241×10 -2The relative value (unit: %) when the conductivity of μΩm) is set to 100%. Regarding the conductivity (%IACS) in the embodiment, test pieces are cut from more than 3 locations of the sample, and the conductivity of these test pieces is measured by the four-terminal method. The measured values of these conductivity are calculated based on the above conversion method to express the average value of these conversion values. It is also possible to prepare any three or more test pieces instead of cutting test pieces from more than 3 locations of a sample to implement the conductivity measurement.
[0030] In the high-strength and high-conductivity Cu-Ag alloy sheet material of the embodiment, the sheet material refers to a member in which the ratio of the width (W) of the cross section to the thickness (T) (W / T ratio) is 1.25 or more when the cross section is observed. At this time, the thickness (T) is preferably 0.01 to 0.8 mm, and the width (W) is preferably 0.2 to 500 mm. The W / T ratio of the cross section of the sheet material is preferably 2 or more, and the thickness (T) is preferably 0.01 to 0.8 mm, and the width (W) is preferably 0.2 to 500 mm. Further, the W / T ratio of the cross section of the sheet material is preferably 5 or more, and the thickness (T) is preferably 0.1 to 0.8 mm, and the width (W) is preferably 5 to 500 mm. Further, the W / T ratio of the cross section of the sheet material is more preferably 10 or more, and the thickness (T) is preferably 0.1 to 0.5 mm, and the width (W) is preferably 5 to 500 mm. The width (W) of the cross section of the sheet material is more preferably 5 to 300 mm. In other words, according to the high-strength and high-conductivity Cu-Ag alloy sheet material of the embodiment, a Cu-Ag alloy sheet material having the above-mentioned cross-sectional shape, tensile strength (UTS) and conductivity (%IACS) can be provided in practice. Here, the sheet material preferably has a rectangular cross section, but is not necessarily limited to this, and may also have an elliptical cross section or a special cross section such as a stepped cross section. In this case, a member having a ratio of width to maximum thickness of 1.25 or more is used as the sheet material.
[0031] A high-strength and high-conductivity Cu-Ag alloy sheet material that satisfies both the above-mentioned tensile strength (UTS) and electrical conductivity (%IACS) can be obtained by applying the manufacturing method of the Cu-Ag alloy sheet material described below. According to the manufacturing method of the Cu-Ag alloy sheet material described below, a fibrous structure in which fibers containing Ag (hereinafter referred to as Ag fibers) exist in a Cu-Ag solid solution can be obtained. Here, the Ag fibers contain a eutectic phase of Cu and Ag. In such a fibrous structure, by (1) controlling the crystal plane of Ag in X-ray diffraction (XRD) and / or (2) controlling the shape and amount of the Ag fibers, the strength and electrical conductivity of the Cu-Ag alloy sheet material can be simultaneously improved, that is, the tensile strength (UTS) of 1000 MPa or more and 1250 MPa or less and the electrical conductivity (%IACS) of 60% or more and 90% or less can be satisfied.
[0032] Regarding the configuration (1), when there is a diffraction peak of the Ag (220) plane in the XRD diffraction pattern of the Cu-Ag alloy sheet having a fibrous structure, and when the peak intensity ratio of the Ag (220) plane is 80% or more, the tensile strength (UTS) and the electrical conductivity (%IACS) can be reproducibly and well balanced. That is, the peak intensity ratio of the Ag (220) plane being 80% or more means that the Ag fibers are present in the Cu-Ag alloy sheet in an appropriate shape and amount, thereby improving both the strength and the electrical conductivity of the Cu-Ag alloy sheet. In contrast, when the peak intensity ratio of the Ag (111) plane exceeds 20%, the amount of the Ag fibers, especially the amount of the coarse Ag fibers described later, becomes excessive, and the strength and the electrical conductivity of the Cu-Ag alloy sheet are reduced. In addition, the workability of the Cu-Ag alloy sheet is also reduced. Therefore, when the peak intensity ratio of the Ag (220) plane is 80% or more and the peak intensity ratio of the Ag (111) plane is 20% or less in the XRD diffraction pattern, the strength and conductivity of the Cu-Ag alloy sheet can be improved simultaneously.
[0033] Here, the peak intensity ratio of the Ag (220) plane and the peak intensity ratio of the Ag (111) plane are measured and specified as follows. That is, a sample of the Cu-Ag alloy plate is irradiated with X-rays by a beam-forming method, and the diffraction peak is detected by a 2θ-θ method. The phases of the diffraction peaks are identified to obtain the intensities of Ag and Cu, respectively. Then, the peak intensity of each crystal plane is converted into a percentage as an intensity ratio. X-ray diffraction based on the 2θ-θ method is implemented using, for example, a test piece with a width of 10 mm, a thickness of 0.2 mm, and a length of 10 mm. However, the size of the test piece is not limited to the above-mentioned shape, and the test piece only needs to be of a size that can be set in an X-ray diffraction device. X-ray diffraction can be implemented using, for example, a test piece with a width of 2 mm, a thickness of 0.2 mm, and a length of 10 mm.
[0034] Regarding configuration (2), when the Cu-Ag alloy sheet has the above-mentioned fibrous structure containing Ag fibers, the Ag fibers contribute to improving the strength of the Cu-Ag alloy sheet. Furthermore, the Ag fibers also contribute to improving the electrical conductivity of the Cu-Ag alloy sheet according to their shape and amount. From these viewpoints, in the fibrous structure containing Ag fibers, it is preferred that fine Ag fibers be present in an appropriate amount. The fine Ag fibers are preferably present in such a manner that the concentration (C1) of the fine Ag fibers in the fibrous structure is greater than 4% and less than 7% in terms of area ratio. By making the area ratio of the concentration of the fine Ag fibers greater than 4%, the strength of the Cu-Ag alloy sheet can be improved. However, when the area ratio of the concentration of the fine Ag fibers exceeds 7%, there is a tendency for the electrical conductivity of the Cu-Ag alloy sheet to decrease. The area ratio of the concentration (C1) of the fine Ag fibers is more preferably greater than 5% and less than 7%.
[0035] In addition, the fibrous structure containing Ag fibers preferably has thick Ag fibers in addition to the above-mentioned fine Ag fibers. The thick Ag fibers are preferably present in a manner that the concentration (C2) of the thick Ag fibers in the fibrous structure is greater than 3% and less than 6% in terms of area ratio. In addition, in the fibrous structure containing Ag fibers, it is preferred that the thin Ag fibers and the thick Ag fibers are present in a manner that the ratio (C1 / C2) of the area ratio of the concentration (C1) of the thin Ag fibers to the area ratio of the concentration (C2) of the thick Ag fibers is greater than 0.9. The thick Ag fibers contribute to the improvement of the strength of the Cu-Ag alloy sheet, and they themselves compensate for the conductivity, and therefore also contribute to the improvement of the conductivity.
[0036] By making the area ratio of the concentration of coarse Ag fibers 3% or more, the strength and conductivity of the Cu-Ag alloy sheet can be improved at the same time. However, when the area ratio of the concentration of coarse Ag fibers exceeds 6%, or the area ratio of the concentration of Ag fibers (C1 / C2) is less than 0.9, the amount of coarse Ag fibers increases excessively, and thus, the strength and conductivity of the Cu-Ag alloy sheet tend to decrease. The area ratio (C1 / C2) of the concentration of Ag fibers is preferably 2 or less. When the area ratio (C1 / C2) of the concentration of Ag fibers exceeds 2, the relative amount of coarse Ag fibers decreases, and the effect of improving the strength and conductivity of the Cu-Ag alloy sheet may become insufficient. The area ratio of the concentration of coarse Ag fibers is more preferably 4% or more and 5.5% or less. In addition, the area ratio (C1 / C2) of the concentration of Ag fibers is more preferably 1 or more and 1.5 or less.
[0037] Here, the thin Ag fiber refers to the Ag fiber showing a fibrous structure whose wire diameter is stretched to more than 0.1nm and less than 1.0nm. In addition, the thick Ag fiber refers to the Ag fiber showing a fibrous structure whose wire diameter is stretched to more than 1μm and less than 10μm. The observation of these thin Ag fibers and thick Ag fibers and the determination of the area ratio (unit: %) of the concentration are implemented as follows. That is, a 5mm square sample is cut out from a Cu-Ag alloy plate using a high cutter, and after mechanical grinding using water-resistant abrasive paper (#2000), the cross-section is ground using an ion milling method, and observed using a field emission scanning electron microscope (FE-SEM). It should be noted that the observation is carried out under the conditions of an acceleration voltage of 5kV, a magnification of 60,000 times, and a COMPO image (composition image), and the fiber diameter is measured based on the observed image, specific Ag fibers, and the observed image is binarized with a threshold value of 10,000 to compare the area ratio. It should be noted that the wire diameter of the Ag fiber represents the thickness in the above cross-sectional observation, and may have a width in the depth direction. The Ag fiber is not limited to the so-called fiber shape, and may also have a plate shape with a certain degree of width. It should be noted that the ratio of the width to the thickness of the above-mentioned plate is for the alloy plate, and is not applicable to the shape of the Ag fiber.
[0038] (Second Embodiment)
[0039] Next, the high-strength and high-conductivity copper alloy sheet material of the second embodiment is described. The high-strength and high-conductivity copper alloy sheet material of the second embodiment is a copper alloy (Cu-Ag alloy) sheet material containing silver (Ag) in the range of 4 mass % or more and 13 mass % or less, and the balance is composed of copper (Cu) and inevitable impurities. When the content of Ag in the Cu-Ag alloy sheet material of the second embodiment is less than 4 mass %, the strength improvement effect brought about by the inclusion of Ag cannot be fully obtained. In terms of further improving the strength of the Cu-Ag alloy sheet material, the content of Ag is preferably 6 mass % or more, more preferably 8 mass % or more, and further preferably 9 mass % or more. When the content of Ag exceeds 13 mass %, the processability is reduced, and it is difficult to manufacture the Cu-Ag alloy sheet material in practice. In terms of further improving the processability of the Cu-Ag alloy sheet material, the content of Ag is preferably 12 mass % or less, and more preferably 11 mass % or less. The content of inevitable impurities, the shape of the plate, the methods for measuring various properties, etc. of the high-strength and high-conductivity Cu-Ag alloy plate of the second embodiment are the same as those of the high-strength and high-conductivity Cu-Ag alloy plate of the first embodiment, and the reasons for their determination are also the same. It should be noted that the Cu-Ag alloy plate of the second embodiment has basically the same configuration as that of the first embodiment except for the configuration described in detail below.
[0040] The high-strength and high-conductivity Cu-Ag alloy sheet material of the second embodiment is characterized in that, in X-ray diffraction (XRD), the peak intensity ratio of the Ag (311) plane is 20% or less. It has been found that in the Cu-Ag alloy sheet material, the Ag (311) plane is a crystal plane that reduces the strength of the Cu-Ag alloy sheet material. By controlling the peak intensity ratio of such an Ag (311) plane to be 20% or less, the strength of the Cu-Ag alloy sheet material containing Ag in the range of 4 to 13 mass % can be improved. In addition, regarding the conductivity of the Cu-Ag alloy sheet material, high conductivity can be obtained by making the Cu-Ag alloy sheet material contain Ag in the range of 4 to 13 mass %. The peak intensity ratio of the Ag (311) plane is preferably 15% or less, more preferably 10% or less, and even more preferably substantially 0%. In the X-ray diffraction of the Cu-Ag alloy plate material, peaks other than the (311) plane are not particularly limited, but include peaks of the (220) plane and the (111) plane described above.
[0041] The peak intensity ratio of the Ag (311) plane is measured and specified as described above. That is, a sample of the Cu-Ag alloy plate is irradiated with X-rays by a beam-forming method, and the diffraction peak is detected by a 2θ-θ method. The phase of the diffraction peak is identified, and the intensities of Ag and Cu are obtained respectively. Then, the peak intensity of each crystal plane is converted into a percentage as an intensity ratio. X-ray diffraction based on the 2θ-θ method is implemented using, for example, a test piece with a width of 10 mm, a thickness of 0.2 mm, and a length of 10 mm. However, the size of the test piece is not limited to the above shape, and the test piece can be of a size that can be set in an X-ray diffraction device. X-ray diffraction can be implemented using, for example, a test piece with a width of 2 mm, a thickness of 0.2 mm, and a length of 10 mm.
[0042] As described above, when the peak intensity ratio of the Ag (311) plane in the XRD diffraction pattern of the Cu-Ag alloy sheet is 20% or less, the tensile strength (UTS) of the Cu-Ag alloy sheet can be improved without impairing the electrical conductivity based on the Cu-Ag alloy composition containing Ag in the range of 4 to 13 mass%. Specifically, a Cu-Ag alloy sheet satisfying a tensile strength (UTS) of 600 MPa or more and 1250 MPa or less and an electrical conductivity (% IACS) of 60% or more and 90% or less can be provided. In other words, when the peak intensity ratio of the Ag (311) plane in XRD exceeds 20%, the tensile strength (UTS) is less than 600 MPa, and the function as a high-strength and high-conductivity Cu-Ag alloy sheet cannot be satisfied.
[0043] According to such a Cu-Ag alloy plate material that takes into account both high strength and high conductivity, a conductive component (plate material) suitable for a bit plate (conductive plate) used in the above-mentioned water-cooled copper magnet, a probe material for a contact probe, a connector material for a portable device, etc. can be provided. For example, a Cu-Ag alloy plate material having a tensile strength (UTS) of more than 600MPa and less than 1000MPa can be applied to a probe material for a contact probe. That is, when the tensile strength (UTS) is more than 600MPa, in addition to satisfying the strength of the probe material that can be applied to the contact probe, the increase in resistance can be suppressed even when the cross-sectional area of the probe is reduced. In addition, the tensile strength (UTS) of the Cu-Ag alloy plate material can also be set to more than 1000MPa and less than 1250MPa, as in the first embodiment. According to the Cu-Ag alloy plate material having such a tensile strength (UTS), in the case of a bit plate applied to a water-cooled copper magnet, in addition to being able to withstand huge electromagnetic stress and water pressure during water cooling, heat generation can be suppressed even when a large current is flowing. Furthermore, when used as a probe material for a contact probe or a connector material, it is possible to suppress an increase in resistance and cope with rapid charging while satisfying practical strength and shape.
[0044] As described above, when a Cu-Ag alloy sheet is produced by a manufacturing process including rolling and heat treatment described later, the tensile strength (UTS) is generally different depending on the direction of pressure application in the rolling process of the sheet manufacturing process, that is, the rolling direction and the direction orthogonal to the rolling direction (the direction at 90° to the rolling direction). The high-strength and high-conductivity Cu-Ag alloy sheet of the second embodiment satisfies a tensile strength (UTS) of 600 MPa or more in either direction of the rolling direction and the direction orthogonal to the rolling direction. In addition, for the high-strength and high-conductivity Cu-Ag alloy sheet of the second embodiment, the minimum value of the tensile strength (UTS) in the rolling direction satisfies 600 MPa or more and 1150 MPa or less, and the minimum value of the tensile strength (UTS) in the direction orthogonal to the rolling direction satisfies 700 MPa or more and 1250 MPa or less. The tensile strength in the rolling direction of the conventional Cu-Ag alloy sheet is low, whereas the tensile strength (UTS) in the rolling direction of the high-strength and high-conductivity Cu-Ag alloy sheet of the embodiment satisfies 600 MPa or more and 1150 MPa or less. Therefore, when the Cu-Ag alloy sheet of the embodiment is used as a conductive member, even when stress and pressure are applied to the conductive member from various directions, such stress and pressure can be withstood.
[0045] In the high-strength and high-conductivity Cu-Ag alloy sheet of the second embodiment, the tensile strength (UTS) is the stress value under the state of applying the maximum load in the tensile test as described above, which represents the ultimate tensile strength (UTS). Regarding the tensile strength (UTS), a test piece (standard test piece) with a width of 10 mm, a thickness of 0.2 mm, and a length of 200 mm is basically used. In the tensile test with the chuck speed set to 100 mm / min, the load is applied until fracture occurs, and the strength (unit: MPa) at the moment when the maximum load is applied is used as the tensile strength (UTS). However, the size of the test piece is not limited to the above-mentioned shape, and a test piece with a width of 2 mm, a thickness of 0.2 mm, and a length of 10 mm can be used, for example. It should be noted that the values of the tensile strength (UTS) in the rolling direction and the tensile strength (UTS) in the direction orthogonal to the rolling direction are set to the values of cutting test pieces from more than 3 places of each sample to implement the tensile test and represent the minimum value of these measured values. It is also possible to prepare any three or more test pieces instead of cutting test pieces from more than 3 places of a sample to implement the tensile test. The value of the tensile strength (UTS) in the unspecified rolling direction represents the minimum value of the measured values of three or more test pieces prepared regardless of the rolling direction. When the rolling direction cannot be specified, the tensile strength (UTS) in one direction and the direction orthogonal to the direction in the sample can be measured respectively, and the direction can be estimated by considering the magnitude of these values.
[0046] For the high-strength and high-conductivity Cu-Ag alloy sheet material of the second embodiment, the conductivity (%IACS) is a reference for indicating the conductivity based on IACS as described above, and is a relative value (unit: %) when the conductivity of the annealed standard soft copper adopted internationally is set to 100%. Regarding the conductivity (%IACS) in the second embodiment, test pieces are cut from more than three locations of the sample, and the conductivity of these test pieces is measured by the four-terminal method. The measured values of these conductivity are calculated based on the above-mentioned conversion method to calculate the conversion value (%IACS), and the average value of these conversion values is expressed. Instead of cutting test pieces from more than three locations of a sample to measure the conductivity, any three or more test pieces may be prepared.
[0047] (Third Embodiment)
[0048] Next, the manufacturing method of the high-strength and high-conductivity copper alloy sheet of the embodiment is described. It should be noted that the high-strength and high-conductivity copper alloy sheet of the embodiment can be obtained by the manufacturing method shown below, but is not necessarily limited to the manufacturing method shown below. The manufacturing method of the high-strength and high-conductivity copper alloy sheet of the embodiment comprises: a process of casting an alloy raw material containing silver in a range of 4 mass % or more and 13 mass % or less, and the balance consisting of copper and inevitable impurities to obtain an ingot; a process of cold rolling the ingot to obtain a first rolled material; a process of performing a solid solution treatment on the first rolled material at a temperature of 700°C or more and less than 780°C to obtain a solid solution treated material; a process of cold rolling the solid solution treated material to obtain a second rolled material; a process of performing a heat treatment on the second rolled material at a temperature of 200°C or more for a range of 8 hours or more and 48 hours or less, thereby performing an aging treatment to obtain an aging treated material; and a process of cold rolling the aging treated material to obtain a third rolled material as a copper alloy sheet. It should be noted that the heat treatment temperature represents the electric furnace setting temperature (the same below).
[0049] In the manufacturing method of the copper alloy sheet material of the embodiment, the casting process of the alloy raw material is not particularly limited. For example, the alloy raw material containing Ag in the range of 4 mass % or more and 13 mass % or less, and the balance consisting of Cu and inevitable impurities is preferably melted in a graphite crucible in a vacuum atmosphere or an inert atmosphere, or melted in a graphite crucible while blowing an inert gas to the surface of the molten liquid using an atmospheric melting furnace, and cast in a graphite or cast iron mold. The surface defects of the outer peripheral surface of the cast Cu-Ag alloy ingot are preferably removed by grinding. The inevitable impurity amount in the Cu-Ag alloy ingot is preferably 0.1 mass % or less, and more preferably 0.01 mass % or less. It should be noted that, in the case of manufacturing the copper alloy sheet material of the first embodiment, an alloy raw material containing Ag in the range of 6 mass % or more and 13 mass % or less, and the balance consisting of Cu and inevitable impurities is used.
[0050] Next, a first cold rolling process is performed to obtain a first rolled material by cold rolling the Cu-Ag alloy ingot. The first cold rolling process is performed to destroy the grains and grain boundaries generated during casting and to improve the effect of the solution treatment performed later. The processing rate in the thickness direction in the first cold rolling process is preferably set to be greater than 5% and less than 20%. When the processing rate in the first cold rolling process is less than 5%, the grains and grain boundaries generated during casting cannot be fully destroyed. In addition, when the processing rate in the first cold rolling process exceeds 20%, the thickness of the plate as a product cannot be ensured, and it is difficult to manufacture a plate for industrial use. It should be noted that the processing rate in the thickness direction in the cold rolling process is a value obtained by "(AB) / A×100(%)" when the thickness of the material before processing is set to A and the thickness of the material after processing is set to B. The processing rates in the second and third cold rolling processes are the same.
[0051] Next, a solution treatment process is performed to obtain a solution treated material by solution treating the first rolled material. The solution treatment process is a process for dissolving Ag into Cu to obtain a supersaturated solid solution (Cu-Ag solid solution). The solution treatment process is performed at a temperature near or below the solidus of the Cu-Ag composition of the alloy raw material. In the case of 4 to 13 mass % Ag-Cu composition, the solution treatment temperature is preferably set to a range of 700 to 780°C, and more preferably set to a range of 740 to 770°C. In addition, the holding time (solution treatment time) at such a temperature is preferably set to 2 to 5 hours. After the heat treatment for the solution treatment, it is preferably quenched to maintain the supersaturated solid solution structure until room temperature. After the solution treatment, it is preferably quenched, and the quenching rate at this time is preferably set to above -700°C / minute.
[0052] Next, a second cold rolling process is performed to obtain a second rolled material by cold rolling the solution treated material after rapid cooling. The second cold rolling process is performed in order to promote the grain boundary reaction type precipitation during aging treatment by applying strain to the grain boundaries. The processing rate in the thickness direction in the second cold rolling process is preferably set to be greater than 20% and less than 99%. When the processing rate in the second cold rolling process is less than 20%, the grain boundary reaction type precipitation during aging treatment cannot be promoted by applying strain to the grain boundaries. In addition, when the processing rate in the second cold rolling process exceeds 99%, the thickness of the plate as a product cannot be ensured, and it is difficult to manufacture a plate for industrial use. In addition, in order to properly control the fibrous structure containing Ag fibers in the plate, it is more preferred to set the processing rate in the second cold rolling process to less than 40%.
[0053] Next, an aging treatment process is performed to obtain an aged material by aging the second rolled material. The aging treatment process is a process for precipitating Cu grains (grains of Cu-Ag solid solution) from a Cu-Ag supersaturated solid solution. It is also sometimes preferred to precipitate Ag fibers in the Cu grains by aging treatment. After the aging treatment, furnace cooling is preferably performed. The aging treatment process is preferably performed by maintaining the material at a relatively low temperature for a long time. Specifically, it is preferred to maintain the material at a temperature of 200°C or more for a period of 8 hours or more and 48 hours or less. Thus, a moderate recrystallized structure can be obtained in a Cu-Ag alloy containing Ag in a range of 4 to 13% by mass. In addition, Ag fibers having a moderate amount and shape can be precipitated according to the conditions. In addition, in a Cu-Ag alloy containing Ag in a range of 8 to 12% by mass, in addition to Ag fibers serving as the basis for thin Ag fibers, Ag fibers serving as the basis for thick Ag fibers can also be precipitated.
[0054] When the aging treatment temperature is lower than 200°C, it is possible that the crystal plane of the Cu-Ag alloy cannot be brought into an appropriate state, or the thick Ag fibers cannot be fully precipitated. The aging treatment temperature is preferably below 450°C, and more preferably below 410°C. Even if the aging treatment time exceeds 48 hours, it is possible that the crystal plane of the Cu-Ag alloy cannot be brought into an appropriate state. However, when the aging treatment temperature exceeds 450°C, for example, it is possible that an appropriate amount of Ag fibers cannot be obtained, and the strength is easily reduced. In addition, when the aging treatment time exceeds 48 hours, the effect of precipitating an appropriate amount of Ag fibers cannot be obtained. The aging treatment temperature is more preferably set to be above 350°C and below 450°C, and the aging treatment time is more preferably set to be above 12 hours and below 24 hours. In addition, with respect to the aging treatment time, it is preferred that the lower the temperature within the above-mentioned temperature range, the longer the time.
[0055] Then, a third cold rolling process is performed to obtain a third rolled material by cold rolling the aging treated material. The third cold rolling process is a process of making the crystal plane of the Cu-Ag alloy in an appropriate state by stretching the crystalline structure generated by the aging treatment along the rolling direction, and rolling to the thickness required by the plate. In addition, by stretching the Ag fibers precipitated in the aging treated material and the precipitates based thereon along the rolling direction, Ag fibers with a moderate wire diameter can be obtained. In particular, in a Cu-Ag alloy containing Ag in the range of 8 to 12 mass%, a structure in which fine Ag fibers and thick Ag fibers exist in a moderate amount can be obtained. The processing rate in the thickness direction in the third cold rolling process is preferably set to 90% or more. When the processing rate in the third cold rolling process is less than 90%, it is possible that the crystal plane of the Cu-Ag alloy cannot be in an appropriate state, or Ag fibers with a moderate wire diameter cannot be fully obtained. In addition, it is possible that a structure in which fine Ag fibers and thick Ag fibers exist in a moderate amount cannot be obtained. The processing rate in the third cold rolling step is more preferably 95% or more.
[0056] The third rolled material obtained by the third cold rolling process is used as a high-strength and high-conductivity copper alloy sheet material of the embodiment. According to the various manufacturing conditions in the above-mentioned manufacturing method, a high-strength and high-conductivity copper alloy sheet material having a tensile strength (UTS) of more than 1000MPa and less than 1250MPa and a conductivity (%IACS) of more than 60% and less than 90% can be obtained. In addition, according to the manufacturing conditions, a high-strength and high-conductivity copper alloy sheet material having a peak intensity ratio of less than 20% on the Ag (311) plane in the diffraction pattern of XRD can be obtained. According to such a high-strength and high-conductivity copper alloy sheet material, a conductive component (sheet material) suitable for a bit plate used in a water-cooled copper magnet, a probe material for a contact probe that is being miniaturized and densified, a connector material for a portable device, etc. can be provided.
[0057] Example
[0058] Next, specific examples of the present invention and their evaluation results are described.
[0059] (Example 1)
[0060] First, an alloy raw material containing 6 mass % of Ag and the remainder consisting of Cu and inevitable impurities is inserted into a graphite crucible for melting. The Cu-Ag alloy melt is cast in a graphite mold to produce a Cu-Ag alloy ingot. The surface of the Cu-Ag alloy is removed by grinding, thereby producing a Cu-Ag alloy billet with a width of 200 mm, a length of 230 mm, and a thickness of 50 mm. Next, the Cu-Ag alloy billet is cold rolled (processing rate: 20%) in a manner to a thickness of 40 mm to obtain a first rolled material. Next, the first rolled material is maintained at a temperature of 760°C for 2 hours for solution treatment, thereby obtaining a solution treated material. After the solution treatment, it is quenched at a cooling rate of -700°C / min. Next, the solution treated material with a thickness of 40 mm is cold rolled (processing rate: 30%) in a manner to a thickness of 28 mm to obtain a second rolled material. Next, the second rolled material was kept at a temperature of 410°C for 20 hours for aging treatment, thereby obtaining an aging treated material. After the aging treatment, furnace cooling was performed. Then, the aging treated material having a thickness of 28 mm was cold rolled (processing rate: 99%) in a manner such that the thickness was 0.28 mm, thereby obtaining a third rolled material as the target Cu-Ag alloy sheet. The obtained Cu-Ag alloy sheet was provided for the characteristic evaluation described later.
[0061] (Example 2)
[0062] First, an alloy raw material containing 8% by mass of Ag and the remainder consisting of Cu and inevitable impurities is inserted into a graphite crucible for melting. The Cu-Ag alloy melt is cast in a graphite mold to produce a Cu-Ag alloy ingot. The surface of the Cu-Ag alloy is removed by grinding, thereby producing a Cu-Ag alloy billet with a width of 200 mm, a length of 230 mm, and a thickness of 50 mm. Next, the Cu-Ag alloy billet is cold rolled (processing rate: 20%) in a manner to a thickness of 40 mm to obtain a first rolled material. Next, the first rolled material is maintained at a temperature of 760°C for 2 hours for solution treatment, thereby obtaining a solution treated material. After the solution treatment, it is quenched at a cooling rate of -700°C / min. Next, the solution treated material with a thickness of 40 mm is cold rolled (processing rate: 30%) in a manner to a thickness of 28 mm to obtain a second rolled material. Next, the second rolled material was kept at a temperature of 410°C for 20 hours for aging treatment, thereby obtaining an aging treated material. After the aging treatment, furnace cooling was performed. Then, the aging treated material having a thickness of 28 mm was cold rolled (processing rate: 99%) in a manner such that the thickness was 0.28 mm, thereby obtaining a third rolled material as the target Cu-Ag alloy sheet. The obtained Cu-Ag alloy sheet was provided for the characteristic evaluation described later.
[0063] (Example 3)
[0064] First, an alloy raw material containing 10% by mass of Ag and the remainder consisting of Cu and inevitable impurities is inserted into a graphite crucible for melting. The Cu-Ag alloy melt is cast in a graphite mold to produce a Cu-Ag alloy ingot. The surface of the Cu-Ag alloy is removed by grinding, thereby producing a Cu-Ag alloy billet with a width of 200 mm, a length of 230 mm, and a thickness of 50 mm. Next, the Cu-Ag alloy billet is cold rolled (processing rate: 20%) in a manner to a thickness of 40 mm to obtain a first rolled material. Next, the first rolled material is maintained at a temperature of 760°C for 2 hours for solution treatment, thereby obtaining a solution treated material. After the solution treatment, it is quenched at a cooling rate of -700°C / min. Next, the solution treated material with a thickness of 40 mm is cold rolled (processing rate: 30%) in a manner to a thickness of 28 mm to obtain a second rolled material. Next, the second rolled material was kept at a temperature of 410°C for 20 hours for aging treatment, thereby obtaining an aging treated material. After the aging treatment, furnace cooling was performed. Then, the aging treated material having a thickness of 28 mm was cold rolled (processing rate: 99%) in a manner such that the thickness was 0.28 mm, thereby obtaining a third rolled material as the target Cu-Ag alloy sheet. The obtained Cu-Ag alloy sheet was provided for the characteristic evaluation described later.
[0065] (Example 4)
[0066] First, an alloy raw material containing 12% by mass of Ag and the remainder consisting of Cu and inevitable impurities is inserted into a graphite crucible for melting. The Cu-Ag alloy melt is cast in a graphite mold to produce a Cu-Ag alloy ingot. The surface of the Cu-Ag alloy is removed by grinding, thereby producing a Cu-Ag alloy billet with a width of 200 mm, a length of 230 mm, and a thickness of 50 mm. Next, the Cu-Ag alloy billet is cold rolled (processing rate: 20%) in a manner to a thickness of 40 mm to obtain a first rolled material. Next, the first rolled material is maintained at a temperature of 760°C for 2 hours for solution treatment, thereby obtaining a solution treated material. After the solution treatment, it is quenched at a cooling rate of -700°C / min. Next, the solution treated material with a thickness of 40 mm is cold rolled (processing rate: 30%) in a manner to a thickness of 28 mm to obtain a second rolled material. Next, the second rolled material was kept at a temperature of 410°C for 20 hours for aging treatment, thereby obtaining an aging treated material. After the aging treatment, furnace cooling was performed. Then, the aging treated material having a thickness of 28 mm was cold rolled (processing rate: 99%) in a manner such that the thickness was 0.28 mm, thereby obtaining a third rolled material as the target Cu-Ag alloy sheet. The obtained Cu-Ag alloy sheet was provided for the characteristic evaluation described later.
[0067] (Example 5)
[0068] First, an alloy raw material containing 13% by mass of Ag and the remainder consisting of Cu and inevitable impurities is inserted into a graphite crucible for melting. The Cu-Ag alloy melt is cast in a graphite mold to produce a Cu-Ag alloy ingot. The surface of the Cu-Ag alloy is removed by grinding, thereby producing a Cu-Ag alloy billet with a width of 200 mm, a length of 230 mm, and a thickness of 50 mm. Next, the Cu-Ag alloy billet is cold rolled (processing rate: 20%) in a manner to a thickness of 40 mm to obtain a first rolled material. Next, the first rolled material is maintained at a temperature of 760°C for 2 hours for solution treatment, thereby obtaining a solution treated material. After the solution treatment, it is quenched at a cooling rate of -700°C / min. Next, the solution treated material with a thickness of 40 mm is cold rolled (processing rate: 30%) in a manner to a thickness of 28 mm to obtain a second rolled material. Next, the second rolled material was kept at a temperature of 410°C for 20 hours for aging treatment, thereby obtaining an aging treated material. After the aging treatment, furnace cooling was performed. Then, the aging treated material having a thickness of 28 mm was cold rolled (processing rate: 99%) in a manner such that the thickness was 0.28 mm, thereby obtaining a third rolled material as the target Cu-Ag alloy sheet. The obtained Cu-Ag alloy sheet was provided for the characteristic evaluation described later.
[0069] (Comparative Example 1)
[0070] First, an alloy raw material containing 4 mass % Ag and the balance consisting of Cu and inevitable impurities is inserted into a graphite crucible for melting. The Cu-Ag alloy melt is cast in a graphite mold to produce a Cu-Ag alloy ingot. The surface of the Cu-Ag alloy is removed by grinding, thereby producing a Cu-Ag alloy billet with a width of 200 mm, a length of 230 mm, and a thickness of 50 mm. Next, the Cu-Ag alloy billet is cold rolled (processing rate: 20%) in a manner to a thickness of 40 mm to obtain a first rolled material. Next, the first rolled material is maintained at a temperature of 760°C for 2 hours for solution treatment, thereby obtaining a solution treated material. Next, the solution treated material with a thickness of 40 mm is cold rolled (processing rate: 30%) in a manner to a thickness of 28 mm to obtain a second rolled material. Next, the second rolled material is maintained at a temperature of 410°C for 20 hours for aging treatment, thereby obtaining an aging treated material. Then, the aging treated material having a thickness of 28 mm was cold rolled (processing rate: 99%) to a thickness of 0.28 mm, thereby obtaining a third rolled material as the target Cu-Ag alloy sheet. The obtained Cu-Ag alloy sheet was subjected to the property evaluation described below.
[0071] (Reference Example 1)
[0072] First, an alloy raw material containing 6% by mass of Ag and the remainder consisting of Cu and inevitable impurities is inserted into a graphite crucible for melting. The Cu-Ag alloy melt is cast in a graphite mold to produce a Cu-Ag alloy ingot. The surface of the Cu-Ag alloy is removed by grinding, thereby producing a Cu-Ag alloy billet with a width of 200 mm, a length of 230 mm, and a thickness of 40 mm. Next, the Cu-Ag alloy billet is maintained at a temperature of 760°C for 2 hours for solution treatment, thereby obtaining a solution treated material. Next, the solution treated material with a thickness of 40 mm is cold rolled (processing rate: 30%) in a manner to obtain a second rolled material with a thickness of 28 mm. Next, the second rolled material is maintained at a temperature of 410°C for 20 hours for aging treatment, thereby obtaining an aging treated material. Then, the aging treated material having a thickness of 28 mm was cold rolled (processing rate: 99%) to a thickness of 0.28 mm, thereby obtaining a third rolled material as the target Cu-Ag alloy sheet. The obtained Cu-Ag alloy sheet was subjected to the property evaluation described below.
[0073] (Reference Example 2)
[0074] First, an alloy raw material containing 6 mass % Ag and the balance consisting of Cu and inevitable impurities is inserted into a graphite crucible for melting. The Cu-Ag alloy melt is cast in a graphite mold to produce a Cu-Ag alloy ingot. The surface of the Cu-Ag alloy is removed by grinding, thereby producing a Cu-Ag alloy billet with a width of 200 mm, a length of 230 mm, and a thickness of 50 mm. Next, the Cu-Ag alloy billet is cold rolled (processing rate: 20%) in a manner to a thickness of 40 mm to obtain a first rolled material. Next, the first rolled material is maintained at a temperature of 760°C for 2 hours for solution treatment, thereby obtaining a solution treated material. Next, the solution treated material with a thickness of 40 mm is cold rolled (processing rate: 30%) in a manner to a thickness of 28 mm to obtain a second rolled material. Next, the second rolled material is maintained at a temperature of 550°C for 0.5 hours for aging treatment, thereby obtaining an aging treated material. Then, the aging treated material having a thickness of 28 mm was cold rolled (processing rate: 99%) to a thickness of 0.28 mm, thereby obtaining a third rolled material as the target Cu-Ag alloy sheet. The obtained Cu-Ag alloy sheet was subjected to the property evaluation described below.
[0075] (Comparative Example 2)
[0076] First, an alloy raw material containing 14% by mass of Ag and the remainder consisting of Cu and inevitable impurities is inserted into a graphite crucible for melting. The Cu-Ag alloy melt is cast in a graphite mold to produce a Cu-Ag alloy ingot. The surface of the Cu-Ag alloy is removed by grinding, thereby producing a Cu-Ag alloy billet with a width of 200 mm, a length of 230 mm, and a thickness of 50 mm. Next, the Cu-Ag alloy billet is cold rolled (processing rate: 20%) in a manner to a thickness of 40 mm to obtain a first rolled material. Next, the first rolled material is maintained at a temperature of 760°C for 2 hours for solution treatment, thereby obtaining a solution treated material. Next, the solution treated material with a thickness of 40 mm is cold rolled (processing rate: 30%) in a manner to a thickness of 28 mm to obtain a second rolled material. Next, the second rolled material is maintained at a temperature of 410°C for 20 hours for aging treatment, thereby obtaining an aging treated material. Then, the aged material having a thickness of 28 mm was cold rolled to a thickness of 0.28 mm (processing rate: 99%). However, processing cracks etc. occurred during rolling, and the third rolled material having a target thickness of 0.28 mm could not be obtained.
[0077] (Comparative Example 3)
[0078] First, an alloy raw material containing 14% by mass of Ag and the remainder consisting of Cu and inevitable impurities is inserted into a graphite crucible for melting. The Cu-Ag alloy melt is cast in a graphite mold to produce a Cu-Ag alloy ingot. The surface of the Cu-Ag alloy is removed by grinding, thereby producing a Cu-Ag alloy billet with a width of 200 mm, a length of 230 mm, and a thickness of 50 mm. Next, the Cu-Ag alloy billet is cold rolled (processing rate: 20%) in a manner to make a thickness of 40 mm to obtain a first rolled material. Next, the first rolled material is maintained at a temperature of 760°C for 2 hours for solution treatment, thereby obtaining a solution treated material. Next, the solution treated material with a thickness of 40 mm is cold rolled (processing rate: 30%) in a manner to make a thickness of 28 mm to obtain a second rolled material. Next, the second rolled material is maintained at a temperature of 550°C for 0.5 hours for aging treatment, thereby obtaining an aging treated material. Then, the aging treated material with a thickness of 28 mm was cold rolled (processing rate: 99%) to a thickness of 0.28 mm, thereby obtaining a third rolled material as the target Cu-Ag alloy sheet. The obtained Cu-Ag alloy sheet was subjected to the characteristic evaluation described below. However, a large number of cracks were generated in the obtained Cu-Ag alloy sheet.
[0079] (Comparative Example 4)
[0080] First, an alloy raw material containing 24 mass % Ag and the remainder consisting of Cu and inevitable impurities is inserted into a graphite crucible for melting. The Cu-Ag alloy melt is cast in a graphite mold to produce a Cu-Ag alloy ingot. The surface of the Cu-Ag alloy is removed by grinding, thereby producing a Cu-Ag alloy billet with a width of 200 mm, a length of 230 mm, and a thickness of 50 mm. Next, the Cu-Ag alloy billet is cold rolled (processing rate: 20%) in a manner to a thickness of 40 mm to obtain a first rolled material. Next, the first rolled material is maintained at a temperature of 760°C for 2 hours for solution treatment, thereby obtaining a solution treated material. Next, the solution treated material with a thickness of 40 mm is cold rolled (processing rate: 30%) in a manner to a thickness of 28 mm to obtain a second rolled material. Next, the second rolled material is maintained at a temperature of 410°C for 20 hours for aging treatment, thereby obtaining an aging treated material. Then, the aged material having a thickness of 28 mm was cold rolled to a thickness of 0.28 mm (processing rate: 99%). However, processing cracks etc. occurred during rolling, and the third rolled material having a target thickness of 0.28 mm could not be obtained.
[0081] (Comparative Example 5)
[0082] First, an alloy raw material containing 24% by mass of Ag and the remainder consisting of Cu and inevitable impurities is inserted into a graphite crucible for melting. The Cu-Ag alloy melt is cast in a graphite mold to produce a Cu-Ag alloy ingot. The surface of the Cu-Ag alloy is removed by grinding, thereby producing a Cu-Ag alloy billet with a width of 200 mm, a length of 230 mm, and a thickness of 40 mm. Next, the Cu-Ag alloy billet is kept at a temperature of 760°C for 2 hours for solution treatment, thereby obtaining a solution treated material. Next, the solution treated material with a thickness of 40 mm is cold rolled (processing rate: 30%) in a manner to a thickness of 28 mm to obtain a second rolled material. Next, the second rolled material is kept at a temperature of 410°C for 20 hours for aging treatment, thereby obtaining an aging treated material. Then, the aging treated material with a thickness of 28 mm is cold rolled (processing rate: 99%) in a manner to a thickness of 0.28 mm. However, processing cracks and the like occurred during rolling, and the third rolled material having the target thickness of 0.28 mm could not be obtained.
[0083] (Comparative Example 6)
[0084] First, an alloy raw material containing 24 mass % Ag and the remainder consisting of Cu and inevitable impurities is inserted into a graphite crucible for melting. The Cu-Ag alloy melt is cast in a graphite mold to produce a Cu-Ag alloy ingot. The surface of the Cu-Ag alloy is removed by grinding, thereby producing a Cu-Ag alloy billet with a width of 200 mm, a length of 230 mm, and a thickness of 50 mm. Next, the Cu-Ag alloy billet is cold rolled (processing rate: 20%) in a manner to a thickness of 40 mm to obtain a first rolled material. Next, the first rolled material is maintained at a temperature of 760°C for 2 hours for solution treatment, thereby obtaining a solution treated material. Next, the solution treated material with a thickness of 40 mm is cold rolled (processing rate: 30%) in a manner to a thickness of 28 mm to obtain a second rolled material. Next, the second rolled material is maintained at a temperature of 550°C for 0.5 hours for aging treatment, thereby obtaining an aging treated material. Then, the aging treated material with a thickness of 28 mm was cold rolled (processing rate: 99%) to a thickness of 0.28 mm, thereby obtaining a third rolled material as the target Cu-Ag alloy sheet. The obtained Cu-Ag alloy sheet was subjected to the characteristic evaluation described below. However, a large number of cracks were generated in the obtained Cu-Ag alloy sheet.
[0085] For the Cu-Ag alloy plates obtained from the above-mentioned Examples 1 to 5, Reference Examples 1 to 2, and Comparative Examples 1, 3, and 6, XRD measurements were performed according to the above-mentioned method to determine the peak intensity ratio of the Ag (220) plane, the peak intensity ratio of the Ag (111) plane, the peak intensity ratio of other Ag planes, and the peak intensity ratio of planes other than the Ag (220) plane. The XRD measurement was performed using an X-ray diffraction device Smartlab (trade name) manufactured by Rigaku Corporation. The XRD measurement results are shown in Table 1. It should be noted that the peak intensity ratio of other Ag planes and the peak intensity ratio of planes other than the Ag (220) plane are determined based on the above-mentioned method for determining the peak intensity ratio of the Ag (220) plane and the Ag (111) plane.
[0086] [Table 1]
[0087]
[0088] Next, the metal structures of the Cu-Ag alloy sheets obtained from the above-mentioned Examples 1 to 5, Reference Examples 1 to 2, and Comparative Examples 1, 3, and 6 were observed and evaluated according to the above-mentioned method. As evaluation results, the concentration (area ratio) of fine Ag fibers, its average value and concentration deviation, the concentration (area ratio) of thick Ag fibers, its average value and concentration deviation, and the ratio of the concentration of fine Ag fibers (average value of area ratio: C1) to the concentration of thick Ag fibers (average value of area ratio: C2) are shown in Table 2. As shown in Table 2, it can be seen that the Cu-Ag alloy sheets of Examples 1 to 5 have Ag fibers of appropriate shapes and amounts, while the Cu-Ag alloy sheet of Comparative Example 1 has a small amount of Ag fibers precipitated due to a small Ag content. Regarding the Cu-Ag alloy sheet of Reference Example 1, it can be seen that since cold rolling after casting was omitted, the solution treatment was not sufficiently completed, and therefore the Ag fibers were not sufficiently precipitated. Regarding the Cu-Ag alloy sheet of Reference Example 2, it is found that Ag fibers of appropriate shape and amount are not precipitated because the aging treatment conditions are set to high temperature. Regarding the Cu-Ag alloy sheets of Comparative Examples 3 and 6, it is found that Ag fibers of appropriate shape and amount are not precipitated because Ag is excessively contained.
[0089] [Table 2]
[0090]
[0091] Next, the electrical conductivity (%IACS), the tensile strength in the rolling direction (UTS), and the tensile strength in the direction perpendicular to the rolling direction (UTS) of the Cu-Ag alloy sheets obtained in Examples 1 to 5, Reference Examples 1 to 2, and Comparative Examples 1, 3, and 6 were measured according to the above method. The measurement results are shown in Table 2. As is apparent from Table 2, the electrical conductivity (%IACS), the tensile strength in the rolling direction (UTS), and the tensile strength in the direction perpendicular to the rolling direction (UTS) of the Cu-Ag alloy sheets of Examples 1 to 4 all showed excellent values.
[0092] [Table 3]
[0093]
[0094] (Examples 6 to 9)
[0095] First, an alloy raw material containing the amount of Ag shown in Table 4 and the remainder consisting of Cu and inevitable impurities is inserted into a graphite crucible for melting. The Cu-Ag alloy melt is cast in a graphite mold to produce a Cu-Ag alloy ingot. The surface of the Cu-Ag alloy is removed by grinding, thereby producing a Cu-Ag alloy billet with a width of 200 mm, a length of 230 mm, and a thickness of 50 mm. Next, the Cu-Ag alloy billet is cold rolled at the processing rate shown in Table 4 to obtain a first rolled material. Next, the first rolled material is solution treated under the conditions shown in Table 4 to obtain a solution treated material. After the solution treatment, it is quenched at a cooling rate of -700°C / min. Next, the solution treated material is cold rolled at the processing rate shown in Table 4 to obtain a second rolled material. Next, the second rolled material is aged under the conditions shown in Table 4 to obtain an aged treated material. After the aging treatment, furnace cooling is performed. Then, the aging treated material was cold rolled at the processing rate shown in Table 4, thereby obtaining a third rolled material as the target Cu-Ag alloy sheet. The XRD measurement, electrical conductivity measurement, and tensile strength (UTS) measurement of the obtained Cu-Ag alloy sheet were carried out in the same manner as in Example 1. The results are shown in Table 5. In the XRD measurement, the peak intensity ratio of the Ag (311) surface was determined. The tensile strength (UTS) was determined for the rolling direction and the direction orthogonal to the rolling direction.
[0096] [Table 4]
[0097]
[0098] [Table 5]
[0099]
[0100] (Examples 10 to 31, Comparative Examples 7 to 9)
[0101] First, an alloy raw material containing the amount of Ag shown in Table 6 and the remainder consisting of Cu and inevitable impurities is inserted into a graphite crucible for melting. The Cu-Ag alloy melt is cast in a graphite mold to produce a Cu-Ag alloy ingot. The surface of the Cu-Ag alloy is removed by grinding, thereby producing a Cu-Ag alloy billet with a width of 200 mm, a length of 230 mm, and a thickness of 50 mm. Next, the Cu-Ag alloy billet is cold rolled at the processing rate shown in Table 6 to obtain a first rolled material. Next, the first rolled material is solution treated under the conditions shown in Table 6 to obtain a solution treated material. After the solution treatment, it is quenched at a cooling rate of -700°C / min. Next, the solution treated material is cold rolled at the processing rate shown in Table 6 to obtain a second rolled material. Next, the second rolled material is aged under the conditions shown in Table 6 to obtain an aged treated material. After the aging treatment, furnace cooling is performed. Then, the aged material was cold rolled at the processing rate shown in Table 6, thereby obtaining a third rolled material as the target Cu-Ag alloy sheet. The XRD measurement, electrical conductivity measurement, and tensile strength (UTS) measurement of the obtained Cu-Ag alloy sheet were carried out in the same manner as in Example 1. The results are shown in Table 7. In the XRD measurement, the peak intensity ratio of the Ag (311) plane was determined. Figure 1 The XRD spectrum of the Cu-Ag alloy plate of Example 29 is shown in Figure 2 ] is an XRD spectrum of the copper alloy sheet material of Comparative Example 9. The tensile strength (UTS) was determined in the rolling direction and in the direction perpendicular to the rolling direction.
[0102] [Table 6]
[0103]
[0104] [Table 7]
[0105]
[0106] Industrial Applicability
[0107] The high-strength and high-conductivity copper alloy sheet of the present invention can be effectively used as conductive components (sheets) such as bit plates used in water-cooled copper magnets, probe materials for contact probes that are being miniaturized and densified, and connector materials for portable devices. In addition, it can also be used in other applications that require high strength and high conductivity.
Claims
1. A high-strength and high-conductivity copper alloy sheet material, comprising silver in a range of 6 mass % or more and 13 mass % or less, with the balance being copper and inevitable impurities, in, In the diffraction pattern of X-ray diffraction of the copper alloy plate material, the peak intensity ratio of the silver (220) plane is 80% or more, and the peak intensity ratio of the silver (111) plane is 20% or less, The minimum value of the tensile strength UTS is 1000 MPa or more and 1250 MPa or less, and the electrical conductivity %IACS is 60% or more and 90% or less, The copper alloy sheet material has a metal structure having fibers containing silver. The metal structure has fine fibers having a linear diameter of 0.1 nm or more and 1.0 nm or less, and a concentration of the fine fibers in the metal structure is 4% or more and 7% or less in terms of area ratio, The copper alloy sheet has a minimum tensile strength UTS in a rolling direction of 1000 MPa to 1150 MPa, and a minimum tensile strength UTS in a direction perpendicular to the rolling direction of 1150 MPa to 1250 MPa.
2. The high-strength and high-conductivity copper alloy sheet material according to claim 1, in, The silver is contained in a range of 8 mass % or more and 12 mass % or less.
3. The high-strength and high-conductivity copper alloy sheet material according to claim 1 or claim 2, in, The electrical conductivity %IACS of the copper alloy sheet material is 64% or more and 75% or less.
4. The high-strength and high-conductivity copper alloy sheet material according to claim 1 or 2, in, The metal structure has fine fibers with a line diameter of not less than 0.1 nm and not more than 1.0 nm and coarse fibers with a line diameter of not less than 1 μm and not more than 10 μm, and the concentration of the fine fibers in the metal structure is not less than 4% and not more than 7% in terms of area ratio, and the concentration of the coarse fibers is not less than 3% and not more than 6% in terms of area ratio, and the ratio of the area ratio of the concentration of the fine fibers to the area ratio of the concentration of the coarse fibers is not less than 0.
9.
5. The high-strength and high-conductivity copper alloy sheet material according to claim 3, in, The metal structure has fine fibers with a line diameter of not less than 0.1 nm and not more than 1.0 nm and coarse fibers with a line diameter of not less than 1 μm and not more than 10 μm, and the concentration of the fine fibers in the metal structure is not less than 4% and not more than 7% in terms of area ratio, and the concentration of the coarse fibers is not less than 3% and not more than 6% in terms of area ratio, and the ratio of the area ratio of the concentration of the fine fibers to the area ratio of the concentration of the coarse fibers is not less than 0.
9.
6. A method for producing a high-strength and high-conductivity copper alloy sheet, comprising: A step of casting an alloy raw material containing silver in a range of 6 mass % or more and 13 mass % or less, with the balance being copper and inevitable impurities, to obtain an ingot; The step of cold-rolling the ingot so that the processing rate from the ingot to the rolled material in the thickness direction is 5% or more and 20% or less to obtain a first rolled material; The step of subjecting the first rolled material to a solution treatment at a temperature of 700° C. or higher and lower than 780° C. to obtain a solution treated material; The step of cold rolling the solution treated material so that the processing rate in the thickness direction is 20% or more and 99% or less to obtain a second rolled material; The step of heat-treating the second rolled material at a temperature ranging from 200° C. to 450° C. for 8 hours to 48 hours to obtain an aged material by aging the material; and A step of cold-rolling the aging treated material to obtain a third rolled material as a copper alloy plate material.
7. The method for producing a high-strength and high-conductivity copper alloy sheet material according to claim 6, in, The rolling step for obtaining the third rolled material is performed so that the processing rate in the thickness direction from the aging treated material to the third rolled material is 90% or more.
8. The method for producing a high-strength and high-conductivity copper alloy sheet material according to claim 6 or claim 7, in, The rolling process for obtaining the first rolled material is carried out in a manner that the processing rate in the thickness direction from the ingot to the first rolled material is greater than 5% and less than 20%, and the rolling process for obtaining the second rolled material is carried out in a manner that the processing rate in the thickness direction from the solution treated material to the second rolled material is greater than 20% and less than 40%.
